Pendampingan Halaqah Tahsin Guna Meningkatkan Kualitas Baca Qur’an Muslimah Sinjai - Suriyati, Suriyati; Suriati, Suriati; Nur, Andi Taufiq; Mytra, Prima; Adillah, Nur (PANRITA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service aims to provide halaqah tahsin assistance to improve the quality of Sinjai Muslim women's reading of the Qur'an. The method for implementing this assistance is divided into three stages, namely (1) The preparation and planning stage, carried out for a week, namely in the form of field observations, entering into a cooperation agreement with the ustazah as the mudarrisah at the halaqah tahsin. (2) The implementation stage is carried out by carrying out a mentoring process for Sinjai Muslim women who learn to improve their reading of the Qur'an (tahsin) guided by the ustazah as mudarrisah. At this stage, before the ustazah delivers the Tahsin material, the ustazah first invites each Muslim woman to take turns reading the Koran starting from juz 30 where at each meeting there will be a revised reading of one to 3 surahs. Then, the ustazah explains the tahsin material in a structured manner to Muslim women as in the tahsin manual while providing example verses so that Muslim women can more easily understand the material. (3) Evaluation and reporting stage where the author evaluates the ability or understanding of Muslim women during the process of improving their reading of the Qur'an in the halaqah tahsin. The results of this halaqah tahsin assistance show an increase in the quality of Qur'an reading among Sinjai Muslim women. After following the assistance in halaqah tahsin, the ability to read the Koran of Sinjai Muslim women gradually improved and became better, in accordance with the rules of tajwid.